Political stability and fiscal policy time series evidence for the Swiss federal level since 1849 - Feld, Lars P.; Schaltegger, Christoph A. (CESifo working papers, 2009)
This paper explores the role of political stability on fiscal policy choices in a time-series analysis over 158 years on the Swiss federal level. We argue that the fiscal-commons problem of public finances is affected by the time-horizon of a finance minister. Arguably, the incentives for an incumbent to maintain a good reputation with sound policy decisions are stronger the longer the time-horizon of a respective term. In addition, a finance minister who succeeds to stay a long time in office normally enjoys a politically powerful position towards the parliament, the administration and the interest groups to influence policy decisions. In contrast, frequent government turnover weakens the position of the finance minister.
Literaturverz. S. 27 - 30
Keywords: 1849-2007; Geschichte 1849-2009; Finanzpolitik; Schweiz